KEPENTINGAN NASIONAL AMERIKA SERIKAT DALAM UNITED STATE AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID)TERHADAP PROGRAM BANTUAN KEMANUSIAAN DI FILIPINA (TOPAN HAIYAN)TAHUN 2013 - Syadiah, Halima Tus; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research purpose is to explain about the interest of USAID as agent in implementingof USA policy through humanitarian assistance program. USAID is the prominent USAgovernment. In giving humanitarian assistance to countries that faces disaster as Philippines.Humanitarian Assistance that is given by USA is not only as caring symbols and giving attentionto other country as the effect of disaster but also as one of politics way used to achieve their aimsin abroad.It is qualitative research with literature study. It explained about USAID program inhumanitarian division that sustained by analyzing of national interest and encouraging USA todo the program. In this study, writer used interest concept by doing soft power to implement it.According to Jack. C. Plano, national interest is really prominent purpose to be example ofdetermining politics in another country.It is found that humanitarian assistance is USA given through USAID to Philippines asthe effect of Toppan Haiyan, USA can improve its reputation in international level. ToPhilippines, humanitarian assistance really help in reconciled its country. To international, USAlooks at the prominent example to another country which influence Sto be good will of USA aftersome of countries as Sudan, Myanmar, and Cuba refused to receive humanitarian assistancefrom USA.Key words: USAID, Humanitarian Assistance, Soft Power, National interest, Good Will.